"Politischer Kapitalismus" und Korruption in Russland - Kagarlitsky, Boris (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2003)
Today the western view of Russia presents the problem of corruption exclusively as a continuation of the old Soviet order. In this chapter it is argued that the present phenomenon of corruption in Russia systemicly emerged from the privatization of state property and the introduction of market relations in the 1990s. The problem of corruption in Russia is a problem of political capitalism. It can only be solved by reforms which change the nature of the system, including above all the return to the state of at least part of the privatised property, while at the same time radically reforming and democratising the political system and the apparatus of rule.